INTER- AND INTRA-OBSERVER AGREEMENT IN THE MILCH AND WEISS SYSTEMS - Lozoya, Sergio Charles (Acta Ortop Bras, 2018)
OBJECTIVE: The aim of this study is to estimate the inter- and intra-observer agreement of the Weiss and Milch classification systems in radiological studies of fractures of the lateral humeral condyle in pediatric patients. METHODS: An agreement study was performed with non-probability sampling of consecutive cases with a sample size of a hundred radiological studies, which were evaluated by three experienced orthopedic surgeons and three resident physicians; following a thorough comparison of both inter- and intra-observer agreements over a six-week period based on the Fleiss’ kappa, which was used to determine the inter- and intra-observer agreement rates of both classifications. RESULTS: The overall reliability of the entire group of evaluators for the Milch classification in the inter-observer evaluation was κ = 0.13, 95% CI, 0.08-0.18, and the intra-observer evaluation was κ = 0.08, 95% CI, 0.06-0.11. For the Weiss classification, the overall evaluation had an inter-observer agreement of κ = 0.53, 95% CI, 0.50-0.57, and an intra-observer agreement of κ = 0.22, 95% CI, 0.20 −0.24. CONCLUSION: In the present study, the Weiss classification system demonstrated greater agreement than the Milch classification; however, the latter may require complementary studies, such as an arthrography to enhance classification accuracy. Level of Evidence II, Diagnostic Studies - Investigating Diagnostic Examination.